2013
DOI: 10.3349/ymj.2013.54.2.445
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Down-Regulates Cathepsin B Expression in Fetal Rat Alveolar Type II Cells Exposed to Hyperoxia

Abstract: PurposeHyperoxia has the chief biological effect of cell death. We have previously reported that cathepsin B (CB) is related to fetal alveolar type II cell (FATIIC) death and pretreatment of recombinant IL-10 (rIL-10) attenuates type II cell death during 65%-hyperoixa. In this study, we investigated what kinds of changes of CB expression are induced in FATIICs at different concentrations of hyperoxia (65%- and 85%-hyperoxia) and whether pretreatment with rIL-10 reduces the expression of CB in FATIICs during hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Recently, it was found that IL-10 treatment inhibited inflammatory cytokines released by fetal mouse lung fibroblasts exposed to mechanical stretch (Hawwa et al 2011) and reduced cell death of alveolar type II cells exposed to hyperoxia (Lee & Kim, 2013). Inhaled IL-10 reduced biotrauma and mortality in a model of ventilator-induced lung injury (Hoegl et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that IL-10 treatment inhibited inflammatory cytokines released by fetal mouse lung fibroblasts exposed to mechanical stretch (Hawwa et al 2011) and reduced cell death of alveolar type II cells exposed to hyperoxia (Lee & Kim, 2013). Inhaled IL-10 reduced biotrauma and mortality in a model of ventilator-induced lung injury (Hoegl et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Foetal rat lungs were obtained from time‐pregnant Sprague–Dawley rats (Daehan Biolink, Eumsung, South Korea) on E19 (term = 22 days). After extraction of foetal lungs and isolation of type II cells was proceeded as described previously Describing briefly, extracted tissues were finely minced and digested with 0.5 mg/ml collagenase type I and 0.5 mg/ml collagenase type IA (Sigma Chemical Co., St. Louis, MO, USA) with vigorous pipetting for 15 min. at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from E19 type II cells exposed to 65%‐hyperoxia for 24 hrs or parallel normoxic samples by a single‐step method and purified further with the Rneasy Mini Kit (Invitrogen, Carlsbad, CA, USA). Fold expressions of the hyperoxic samples relative to the controls were calculated using the ΔΔC T method for relative quantification as described previously . Samples were normalized to the 18S rRNA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations